Ancient mitogenomes show plateau populations from last 5200 years partially contributed to present-day Tibetans. Issue 1923 (25th March 2020) - Ding, Manyu; Wang, Tianyi; Ko, Albert Min-Shan; Chen, Honghai; Wang, Hui; Dong, Guanghui; Lu, Hongliang; He, Wei; Wangdue, Shargan; Yuan, Haibing; He, Yuanhong; Cai, Linhai; et al.
Abstract : The clarification of the genetic origins of present-day Tibetans requires an understanding of their past relationships with the ancient populations of the Tibetan Plateau. Here we successfully sequenced 67 complete mitochondrial DNA genomes of 5200 to 300-year-old humans from the plateau. Apart from identifying two ancient plateau lineages (haplogroups D4j1b and M9a1a1c1b1a) that suggest some ancestors of Tibetans came from low-altitude areas 4750 to 2775 years ago and that some were involved in an expansion of people moving between high-altitude areas 2125 to 1100 years ago, we found limited evidence of recent matrilineal continuity on the plateau. Furthermore, deep learning of the ancient data incorporated into simulation models with an accuracy of 97% supports that present-day Tibetan matrilineal ancestry received partial contribution rather than complete continuity from the plateau populations of the last 5200 years.